Effect of pretreatments and packaging materials on the quality of minimally processed cauliflower (Brassica oleracea var. botrytis) - NEELAVATHI, R; PAL, R K; SHANKARASWAMY, J (The Indian Journal of Agricultural Sciences, 2016)
A research study was carried out on Minimal processing of cauliflower in the Division of Post Harvest Technology, Indian Agricultural Research Institute, New Delhi. Pre-treatment of cauliflower florets with 150 ppm sodium hypochlorite for 2 minutes were found to be effective in reducing the bacterial population. Dipping of florets in 1% citric acid for 5 minutes was found to be highly effective in checking bacterial population (3.65 log cfu/g) in the minimally processed cauliflower. The maximum retention of firmness (18.08 N) was found in 1 % CaCl2 treated cauliflower followed by 0.5 % citric acid + 0.5 % CaCl2. The minimally processed cauliflower treated with 150 ppm sodium hypochlorite for 2 minutes and 1 % citric acid for 5 minutes, packed in HDPE (500 gauge), LDPE (100 gauge) and PP (100 gauge) and stored at 5o C for 20 days. The least weight loss was observed in the cauliflower stored in HDPE (2.35%). The respiratory rate and ethylene evolution was higher in cauliflower stored in LDPE packaging than HDPE. During storage, sinigrin content was found to be the higher in cauliflower packed in HDPE films (55.78 μmol/100 g) followed by LDPE (43.74 μmol /100 g). Cauliflower florets packed in HDPE retained significantly higher level of ascorbic acid (43.49 mg/100 g) and firmness (15.92 N). The electrolyte leakage was found to be lower in HDPE (29.5%). The microbial population of minimally processed cauliflower was found to be below the safe level even after 20 days of storage.